Using Detection Dogs to Monitor Aquatic Ecosystem Health and Protect Aquatic Resources (Springer International Publishing, 2018)
This book is about the varied range of emerging applications using specially trained detection dogs to monitor and protect aquatic ecosystems, animals, plants and related resources. Featuring contributions from those at the forefront of converging disciplines ranging from canine training, ecological and biological monitoring, water resource management, law enforcement, and eco-toxicology, it addresses everyone already immersed in these or related fields, and anyone seeking to gain a broader understanding of them. Chapters cover several common themes including monitoring presence/absence through biological and ecological surveys; maintaining and evaluating water quality; law enforcement and anti-poaching initiatives; public education, awareness and compliance; standards and best practices; optimal uses of dogs in relation to and in conjunction with other available tools and pragmatic considerations for selecting and working with dogs and handlers. The aim of the book is to stimulate new ideas, promote the sharing and dissemination of information and findings - and, ideally, to catalyze new and innovative partnerships, to strengthen the preservation and conservation of our aquatic heritage.